Provision of feedback on perceived health status to health care professionals: a systematic review of its impact. - Espallargues, M; Valderas, J; Alonso, J (2000)
OBJECTIVE: To assess the impact on the process and the outcomes of care of feeding back information on perceived health status to health care professionals in clinical practice. DESIGN: Systematic review of controlled trials. DATA IDENTIFICATION: Search in electronic databases (MEDLINE 1966-1997), manual searches, and requests to experts in the field. DATA ANALYSIS: Differences between intervention and control group were considered in process of care (use of health services, diagnosis, and treatment), patient outcomes (health status), and patient satisfaction. In a subgroup of 13 interventions that dealt with the provision of feedback about the patient's mental health, the impact on the process of care was subjected to meta-analysis. RESULTS: We identified 21 studies that satisfied the selection criteria. Eleven of 20 (55%) found significant differences (P <0.05) in at least 1 of the process indicators in favor of the intervention group. Of 11 trials that assessed patient outcomes, only 4 (36%) detected significant improvements. A similar trend but lower percentages were observed among the 8 interventions that provided general health status information. Eleven interventions that evaluated feedback information about the patient's mental health status showed a higher rate of diagnosis in the intervention group (combined odds ratio [OR]=1.91; 95% confidence interval [CI] 1.28 to 2.83). Seven of 9 studies evaluating treatment failed to show an effect on this indicator (combined OR=1.15; 95% CI 0.76 to 1.75). CONCLUSIONS: The provision of feedback on perceived health status to health professionals seems to have an effect on the process of care but not on patient functional or health status. This is especially true with regard to mental health status information. Nevertheless, there is still need for a more through evaluation of this type of intervention.